PENERAPANTEORI BELAJAR DAN DESAIN INSTRUKSIONAL MODEL PADA KETERAMPILAN MENULIS BAHASA INGGRIS - Yulia Yulia (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
Writing is one of skill that students should be mastered beside other skill such as listening, speaking and reading skill. Writing is a complex skill, because to be success in writing the st udent should be mastered complex grammar, they should have many vocabularies, conjunction, punctuation, spelling and mechanical in writing. Learning theories provides the foundation for the selection of instructional strategies. Here the major learning theories are discussed and selected examples of instructional design models are explained. The main objectives of this article is to present instructional design model for EFL students’ writing skill, Learning theory, and some previous instructional design model as theoretical evidence for design and delivery of instructional materials. In  addition, this article provides a design for EFL writing skill material development.Keywords: EFL writing skill, Learning theories, Instructional design, Instructional Design model